Instrumental accompaniment variables in Iraqi music (Journal of the College of Basic Education, 2022)
Each people has constants and intellectual and social variables that reflect negatively or positively on their artistic and musical civilization in particular, because of the direct connection of musical art to social life throughout the ages, and the musical instrument that accompanies their music, as they are the result of their civilizational development and cultural communication between the people of their society and other societies, and therefore they may reflect This musical instrument has its variables on the society itself, so the development of peoples through their art is a reciprocal issue between the outputs of each civilization and its maker, and because the new generation demands everything that is new, it must follow variables imposed by the new reality, affecting it negatively or positively, which constitutes a kind of conflict between originality and urbanization. Which calls us to study the new reality from the musical point of view in order to realize these variables and their impact on the future